2014
DOI: 10.5430/elr.v3n2p54
|View full text |Cite
|
Sign up to set email alerts
|

Bilingualism and Creative Abilities in Early Childhood

Abstract: The present study was motivated by a scarcity of knowledge about the impact of early bilingualism on the development of general creativity and mathematical creativity. Two groups of bilingual and monolingual preschoolers (mean age = 60.9 months, SD= 3.1) from the same monolingual kindergarten participated in this study: 15 Russian/Hebrew balanced bilinguals and 15 native Hebrew-speaking monolinguals. All children were administered the Figural Form A (Thinking Creatively with Pictures) from the Torrance Tests o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
(51 reference statements)
2
9
0
Order By: Relevance
“…These studies verify that there is a domain-general part of creativity, perhaps related to insight or divergent thinking (Mumford and Gustafson 1988;Plucker 1999). However, as others have found, most variance is explained by specific abilities (Chen et al 2006;Leikin 2014;Sawyer 2006). For instance, a very creative mathematician is not necessarily creative in another domain such as writing.…”
Section: Domain-general Creativity and Mathematical Ability In Relatisupporting
confidence: 69%
“…These studies verify that there is a domain-general part of creativity, perhaps related to insight or divergent thinking (Mumford and Gustafson 1988;Plucker 1999). However, as others have found, most variance is explained by specific abilities (Chen et al 2006;Leikin 2014;Sawyer 2006). For instance, a very creative mathematician is not necessarily creative in another domain such as writing.…”
Section: Domain-general Creativity and Mathematical Ability In Relatisupporting
confidence: 69%
“…On the one hand, students with a high level of bilingualism obtained significantly better scores than those with a low or medium level in figural creativity (originality, fluency, and flexibility); however, this did not occur for figural elaboration. These results are similar to those obtained by Leikin et al (2014), who found significant differences in all variables of figural creativity, except for elaboration. On the other hand, students with a high level of bilingualism also scored significantly higher than those with a medium level of verbal creativity (originality, fluency, and flexibility).…”
Section: Discussionsupporting
confidence: 92%
“…To date, several studies have found an advantage of bilingualism in different components of verbal and figural creativity: Originality, fluency, and flexibility (e.g., Kharkhurin, 2011, 2017; Lasagabaster, 2000; Leikin et al, 2014; Ródenas Ríos et al, 2016). Consistently, the results of the present study largely confirm the main hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On exploring relationship among different degrees of bilingualism and creativity (adaptive creative style, innovative creative style, and creative strengths) it was revealed that the degree of bilingualism was positively associated with creativity, and more specifically, with the adaptive creative style and creative strengths [35]. After examining the relationship between language learning strategies and EFL learners' creativity authors concluded that there is significant relationship between EFL learners total use of language learning strategies and their creative abilities [36].A study conducted to discover the impact of bilingualism on the development of creativity in general and mathematical creativity in particular indicated that the bilingual children depicted higher creative abilities than the monolingual children [37]. A research study conducted on college learners indicated that students who had successfully completed a college level second language courses showed high and positive relation with domains of creativity (fluency, flexibility, originality, elaboration) , whereas students who had not taken second language courses tend to show opposite relation to creativity measures [38].…”
Section: Monolingualismmentioning
confidence: 99%